Evaluation of RANS and LES turbulence models for simulating a steady 2-D plane wall jet. Issue 1 (5th March 2018) - Yan, Zhitao; Zhong, Yongli; Lin, William E.; Savory, Eric; You, Yi
Abstract : Purpose: This paper examines various turbulence models for numerical simulation of a steady, two-dimensional (2-D) plane wall jet without co-flow using the commercial CFD software (ANSYS FLUENT 14.5). The purpose of this paper is to decide the most suitable and most economical method for steady, 2-D plane wall jet simulation. Design/methodology/approach: Seven Reynolds-averaged Navier–Stokes (RANS) turbulence models were evaluated with respect to typical jet scaling parameters such as the jet half-height and the decay of maximum jet velocity, as well as coefficients from the law of the wall and for skin friction. Then, a plane wall jet generating from a rectangular slot of 1:6 aspect ratio located adjacent to the wall was investigated in a three-dimensional (3-D) model using large eddy simulation (LES) and the Stress-omega Reynolds stress model (SWRSM), with the results compared to experimental measurements. Findings: The comparisons of these simulated flow characteristics indicated that the SWRSM was the best of the seven RANS models for simulating the turbulent wall jet. When scaled with outer variables, LES and SWRSM gave generally indistinguishable mean velocity profiles. However, SWRSM performed better for near-wall mean velocity profiles when scaled with inner variables. In general, the results show that LES performed reasonably well when predicting the Reynolds stresses. Originality/value: The main contribution of this article is in determining the capabilities of different RANS turbulence closures and LES for the prediction of the 2-D steady wall jet flow to identify the best modelling approach.